Enhanced biodegradation and detoxification of malachite green by Trichoderma asperellum laccase: Degradation pathway and product analysis. (November 2017) - Shanmugam, Sabarathinam; Ulaganathan, Priyadharshini; Swaminathan, Krishnaswamy; Sadhasivam, Subramaniam; Wu, Yi-Rui
Abstract: The central composite design (CCD)-based response surface methodology (RSM) was engaged in optimizing the biodegradation process of malachite green (MG), a potentially toxic dye, by a laccase identified from Trichoderma asperellum with various parameters viz ., enzyme concentration, dye concentration, reacting pH and incubation time. The maximal degradation of MG was obtained to be 97.18% under the optimum conditions with the enzyme concentration of 1.50 U/mL, the dye concentration of 122.66 mg/L, pH of 6.75and the incubation time of 98.58 min. The kinetics investigation of MG degradation was studied at various concentrations of MG, and the values of K m and V max were determined as 87.50 mg/L and 1.28 mg/L/min, respectively. Through the UV-Visible spectroscopy, FTIR, HPLC and GC-MS/MS analysis, the metabolites during the biodegradation of MG were identified to include Michler's ketone, 4-(dimethylamino)benzophenone, 4-aminobenzophenone and 4-(dimethylamino)benzaldehyde, indicating that the hydroxylation, oxidation, deamination and demethylation processes were all involved in this laccase-mediated MG degradation without the formation of leuco-malachite green derivatives. The genotoxicity studies using the Allium cepa assay have further confirmed that the metabolites are less minimally toxic than the untreated MG. Therefore, this T. asperellum laccase-mediated dye degradation possesses the potentially promising biotreatment process. Highlights: The degradation of MG was improved to be 97.18% without any redox mediators. Optimal variables of T. asperellum laccase-mediated MG degradation were obtained. MG was transformed into benzaldehyde via the Michler's ketone pathway. Metabolites were determined to be less toxic by the genotoxicity analysis.